Peace of mind in the Qur'an: Analysis of the Tafsir Hada'iq al-Rūḥ wa al-Rayḥān by Muhammad Amin al-Harari - Sitii Fathiyyah; Hana Natasya (PT. Student Rihlah Indonesia, 2026)
The pressures of modern life often give rise to anxiety and restlessness that disrupt inner peace. The Qur’an offers a spiritual solution through remembrance (dhikr) and closeness to Allah, as stated in QS. Al-Ra’d [13]: 28. This study aims to analyze the interpretation of verses related to inner peace in Tafsir Hada’iq al-Rūḥ wa al-Rayḥān by Shaykh Muhammad Amin al-Harari and to examine its relevance to the Sufi thought of Ibn Qayyim al-Jawziyyah in Madārij al-Sālikīn. This research employs a qualitative method with a library research approach, analyzed descriptively and analytically through the lens of Islamic psychology and Sufi theory. The findings reveal five core values that contribute to achieving inner peace: sakīnah, tawakkul, ṣabr, riḍā, and shukr, all interpreted through a Sufi lens and aligned with the stages of spiritual development as outlined by Ibn Qayyim. The integration of contemporary exegesis and classical Sufism offers a new contribution to the field of thematic Qur’anic studies and Islamic psychology, particularly in addressing the spiritual needs of Muslims in the modern era.